Development of Monitoring System using Raspberry Pi with Instant Notification - Mazlan, Sazwan Syafiq; Mohamed , Norazlina; Majid, Fatin Faqihah (Journal of Emerging Technologies and Industrial Applications, 2023)
Theft causes damage, loss of property, and emotional misery. Due to the alarmingly high rate of theft that takes place every day, everyone needs a security system to secure their belongings. With the use of a Raspberry Pi 4 Model B, a camera module, and a motion sensor, this project seeks to create a low-cost surveillance system that can capture video and identify movements in restricted areas such as user belongings and property. The algorithms used in this research include dynamic programming algorithm (DPA) and application programming interface (API). The results of the study show that when a motion detector detects an intruder within a range of 0 to 2 meters, an IoT system will immediately send email and Telegram notifications with a ten-second video attachment. The status of the Internet Network Connection affects how quickly the alert is sent. It is projected that the utility of this surveillance system will help reduce the theft rate in Malaysia because of the immediate warning, which permits immediate action, remote monitoring, and the presence of proof in the form of video recordings.